Burnout Syndrome Among Anesthesia Providers Working in Public Hospitals in Rwanda: A Cross-Sectional Survey. (15th September 2022) - Tuyishime, Eugene; McIsaac, Daniel I.; Mumbwe, Mbangu C.; Ruhato Banguti, Paulin; Mvukiyehe, Jean Paul; Nzarora, Josue; Bould, M. Dylan
Abstract : BACKGROUND: Many studies address anesthesia provider burnout in high-income countries; however, there is a paucity of data on burnout for anesthesia providers in low-income countries (LICs). Our objectives were (1) to evaluate the prevalence of burnout among anesthesia providers in Rwandan hospitals and (2) to determine factors associated with burnout among anesthesia providers in Rwandan hospitals. METHODS: A questionnaire was sent to selected Rwandan anesthesia providers working in public hospitals. The questionnaire assessed burnout using the Maslach Burnout Inventory Human Services Survey, a validated 22-item survey used to measure burnout among health professionals. Sociodemographic and work-related factors found to be associated with burnout were also assessed using logistic regression in a Bayesian framework to estimate odds ratios (OR) and associated credible intervals (CrIs). RESULTS: Surveys were distributed to 137 Rwandan anesthesia providers; 99 (72.3%) were returned. Sixty-six (67%) respondents were nonphysician anesthesia providers. Burnout was present in 26 of 99 (26.3%) participants (95% confidence interval [CI], 17.9–36.1). When considering weakly informative priors, we found a 99% probability that not having the right team (OR, 5.36%; 95 CrI, 1.34–23.53) and the frequency of seeing patients with negative outcomes such as death or permanent disability (OR, 9.62; 95% CrI, 2.48–42.84) were associated with burnout. CONCLUSIONS: In a cross-sectional survey of anesthesia providers in Rwanda, more than a quarter of respondents met the criteria for burnout. Lacking the right team and seeing negative outcomes were associated with higher burnout rate. These identified factors should be addressed to prevent the negative consequences of burnout, such as poor patient outcomes.